The Effect of Digital Transformation On The Revitalization of Msmes In Pandemi Time With Digital Literacy As An Intervening Variable (Case Study of Micro Enterprises in the City of Bukittinggi) - Dhea Ananda Puteri; Asyari Asyari (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
This study analyzes whether the application of digital transformation affects the revitalization of MSMEs during the pandemic and whether it can be mediated by digital literacy. Using a sample of 378 respondents from micro-sector MSMEs in Bukittinggi City in 2021, this study reveals that the application of digital transformation and digital literacy is positively related to the revitalization of MSMEs, which in this case uses business performance indicators to serve as a basis for determining the level of success. from the revitalization of SMEs. This finding offers empirical evidence about the importance of digital literacy in the relationship between implementing digital transformation and revitalizing MSMEs during the pandemic. This shows that the implementation of digital transformation will not succeed without an educational intermediary for digital technology itself. Furthermore, this study recommends strategies to improve the application of digital transformation for MSME business actors by increasing digital literacy of business actors